OPTIMIZING VILLAGE POTENTIAL THROUGH THE UTILIZATION OF PRODESKEL APPLICATION TECHNOLOGY IN KEPER VILLAGE, KREMBUNG DISTRICT, SIDOARJO REGENCY - Dewi, Kurnia Candra; Choiriyah, Ilmi Usrotin (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to identify strategies that can be implemented by the village government to maximize the utilization of the Prodeskel application technology. Method: This research is a descriptive qualitatvive study. The informant in this study is the Secretary of Keper Village. Data collection techniques were carried out through interviews, observation, and documentation. The focus of this research is the optimization of village potential through the utilization of the Prodeskel application technology using three indicators: goals, decision alternatives, and limited resource. The data analysis by Miles & Huberman. Results: The optimization of the Prodeskel application in Keper Village demonstrates clear objectives in improving the digital data system, transparency, and the development of village potential, particulary in the agricultural sectors of rice and melon. The chosen alternative strategy, namely training, has not been implemented consistently, with a significant time gap since 2022-2023, thus requiring evaluation and strategic adjustments. Despite limited resources in terms of human resources, time, and constantly changing regulatrions, the village government has shown organizational resilience by continuing to optimize the use of Prodeskel in accordance with the local context and capacity. Novelty: The study highlights the resilience and adaptive capacity of a village government in optimizing digital application technology (Prodeskel) for local development, particularly under constraints of limited resources and evolving regulations, which has not been extensively documented in prior research.